Simulated Activity But Real Trauma. Issue 12 (March 2015) - Müller, Sebastian A.; Vavken, Patrick; Pagenstert, Geert; Polisner., Stuart Barry
<x xml:space="preserve">Abstract</x> Abstract Video gaming injuries are classically regarded as eccentric accidents and novelty diagnoses. A case of an anterior cruciate ligament (ACL) tear sustained during Wii boxing spurned us to review the literature for other Wii-related injuries and Wii-based posttraumatic rehabilitation. The English literature listed in PubMed was systematically reviewed by searching for "Wii (trauma or injury or fracture)." Full-text articles were included after duplicate, blinded review. The type and treatment of injury as well as the Wii-based rehabilitation programs found were analyzed. Additionally, a new case of an acute ACL tear-sustained playing, Wii boxing, is additionally presented. After exclusion of irrelevant articles, 13 articles describing Wii-related injuries were included reporting on 3 fractures, 6 nonosseous, 2 overuse injuries, and 2 rehabilitation programs using Wii for posttraumatic rehabilitation. Among the presented Wii-related injuries, only 12.5% were treated conservatively, whereas 87.5% underwent either surgical or interventional treatment. Because of the reported case, the literature search was limited to Wii-related injuries excluding other video games. Another limitation of this article lies in the fact that mainly case reports but no controlled trials exist on the topic. Assumingly, primarily the more severe injuries are reported in the literature with an unknown number of possibly minor injuries. Motion-controlled video games, such as Wii, are becoming increasingly popular as a recreational entertainment. Because of their wide acceptance and entertaining nature, they are also increasingly recognized as a tool in rehabilitation. However, although the activity is simulated, injuries are real. Our systematic review shows that Wii gaming can lead to severe injuries, sometimes with lasting limitations.